Nutrigenomics of inward rectifier potassium channels - Ferreira, Gonzalo; Santander, Axel; Cardozo, Romina; Chavarría, Luisina; Domínguez, Lucía; Mujica, Nicolás; Benítez, Milagros; Sastre, Santiago; Sobrevia, Luis [UNESP]; Nicolson, Garth L. (Elsevier, 2023)
Inwardly rectifying potassium (Kir) channels play a key role in maintaining the resting membrane potential and supporting potassium homeostasis. There are many variants of Kir channels, which are usually tetramers in which the main subunit has two trans-membrane helices attached to two N- and C-terminal cytoplasmic tails with a pore-forming loop in between that contains the selectivity filter. These channels have domains that are strongly modulated by molecules present in nutrients found in different diets, such as phosphoinositols, polyamines and Mg2+. These molecules can impact these channels directly or indirectly, either allosterically by modulation of enzymes or via the regulation of channel expression. A particular type of these channels is coupled to cell metabolism and inhibited by ATP (KATP channels, essential for insulin release and for the pathogenesis of metabolic diseases like diabetes mellitus). Genomic changes in Kir channels have a significant impact on metabolism, such as conditioning the nutrients and electrolytes that an individual can take. Thus, the nutrigenomics of ion channels is an important emerging field in which we are attempting to understand how nutrients and diets can affect the activity and expression of ion channels and how genomic changes in such channels may be the basis for pathological conditions that limit nutrition and electrolyte intake. In this contribution we briefly review Kir channels, discuss their nutrigenomics, characterize how different components in the diet affect their function and expression, and suggest how their genomic changes lead to pathological phenotypes that affect diet and electrolyte intake.
Keywords: Inward rectifier potassium channels; Ion channels; Metabolism; Nutrigenomics; Potassium channels